Teaching styles: a descriptive study from teaching practice - Burbano-Larrea, Pablo (2021)
The educational institutions involve people in different roles: authorities, teachers, students and parents. The teachers in their professional practice develop a style that distinguishes them by the way they teach and how they evaluate, seeking to consolidate the learning of their students. Knowing the teaching styles of the teachers in an institution allows us to characterize it and develop strategies to achieve academic goals. The objective of this research was to identify the teaching styles that are present among the teachers of the Faculty of Philosophy, Literature and Educational Sciences of the Central University of Ecuador. It had a quantitative approach and a descriptive level, being a transversal study. The conclusions point out that the majority of the teachers have a defined dynamic teaching style. When integrating the results between the analytical and systematic styles, it was found that the majority of teachers have characteristics of rather traditional styles. It was also found that in teaching practice, combined styles such as the analytical-systematic and the dynamic-practical are observed. Among the teachers researched, women show prevalence in the dynamic teaching style, while men mostly have an analytical teaching style. It seems that the semester in which a professorship is given also determines the style used, since differences have been found between higher and lower levels of education.